Relationship between Impulsivity, Social Media Usage and Loneliness - Mustafa Savci; Ferda Aysan (Educational Process: International Journal)
The purpose of this study is to examine the relationships between impulsivity, social media usage, and loneliness and to test the structural hypothetical model developed based on the literature. The study was conducted on 307 (164 female, 143 male) university students. Data collection instruments of the study were the Barratt Impulsivity Scale Short Form (BIS-11-SF), Social Media Usage Scale (SMUS), and UCLA Loneliness Scale Short Form (ULS-8). The measurement models of the latent variables were tested initially and it was observed that the scales of the latent variables were efficient enough to be included in the structural equation model. In addition, the suggested hypothetical model was tested. According to the analysis, it was observed that impulsivity directly, positively and significantly predicts social media usage, that social media usage directly, positively and significantly predicts loneliness, and that impulsivity indirectly, positively and significantly predicts loneliness.